KAJIAN PROSES PEMBUATAN BERAS ANALOG DARI TEPUNG KOMPOSIT DAN TEPUNG TULANG SAPI DENGAN PENAMBAHAN CARBOXYMETHYLCELLULOSE SERTA UJI HEDONIK - Indah K Sihombing; Albiner Siagian; Posman Sibuea (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Rice consumption of the Indonesian population is the highest compared with other countries. Rice consumption of Indonesia's population in 2014 was 114 kg / capita / year. The high consumption of rice resulted in high imports of rice. Food diversification program being promoted Ministry of Agriculture to reduce dependency paddy rice consumption led to new innovations, namely artificial rice. The research is experimental research with experimental design used was completely randomized design. Formulation A1 (composite flour 95% and flour bone cow 5%),  A2 (composite flour 90% and flour bone cow10%), A3 (composite flour 85% and  flour bone cow 15%). Thisresearch uses the hedonictest and proximate test to determine their nutritional content. Hedonic assessment on artificial rice include colour, aroma, texture, and flavor. Hedonic assessment conducted with the 30 panelists. Analysis of data is using descriptive analysis, paired analysis of variance (Repetead ANOVATest) and Friedman Test. on the third treatment artificial rice from processing of composite flour and flour bone cow was produce artificial rice approaching rice. The results of hedonic test based on colour, aroma, texture, and flavor on the third treatment is same that is rather like criteria. The results of Repeated ANOVA test for colour and Friedman test for aroma, texture, and flavor was produced p > 0,05, it means there is no significant difference between samples on the indicator of colour, aroma, texture, and flavor. Artifial rice 3 in a dish once ate as much as 100 grams or 150 grams of rice donated 449 kcal of  total energy.         Artificial rice is highly recommended because it can meet the daily nutritional requirements of individuals and suggested an option staple food.  Keywords: artificial rice, composite flour, flour bone cow, Hedonic assessment